Accuracy and speed of molecular response reporting with Xpert BCR-ABL Ultra in vitro diagnostic test in CML patients - Stangler Herodež Špela; Kokalj-Vokač Nadja; Roškar, Zlatko; Dreisinger, Mojca (Acta Medico-Biotechnica, 2021)
Purpose: The objective of this study was to introduce the GeneXpert Ultra cartridge-based BCR-ABL diagnostic test into routine molecular monitoring of minimal residual disease for chronic myeloid leukemia (CML) patients who are on tyrosine kinase inhibitors (TKIs). Methods: BCR-ABL1 transcript quantification was performed on 100 peripheral blood samples from 33 CML patients at different stages of the disease using automated GeneXpert BCR-ABL Ultra assay and following a standardized laboratory protocol (SP). Results: Analysis results were expressed as % on the International Scale (IS) for BCR-ABL1 real-time PCR quantification and estimated using molecular response (MR) according to the laboratory recommendations for scoring deep MRs following CML treatment. A comparison of the two methods showed that there was no statistically significant difference in the results expressed as % on the IS (p = 0.098). Samples were divided into six groups (MR1, MR2, MR3, MR4, MR4.5, and MR5) according to the estimated MR. A total of 74/100 samples had a completely identical MR with both methods, 12/100 samples had a higher MR obtained with GeneXpert, and 14/100 samples had a lower MR compared to the SP. In addition, 2/74 samples had a different MR for two classes obtained with GeneXpert compared to the SP, while the others 72/74 samples differed in one MR class. Analysis of the major molecular response resulted in 82% agreement. Minimal amounts of BCR-ABL1 copies were detected with GeneExpert in eight samples while the SP did not detect them. None of the GeneXpert results had any effect on the clinical decision for treatment with TKIs obtained using the SP. Conclusion: The Xpert BCR-ABL Ultra assay can be considered a useful and very fast clinical tool for molecular follow up of patients on TKIs.